2018
DOI: 10.1007/s00330-018-5703-9
|View full text |Cite
|
Sign up to set email alerts
|

Initial clinical evaluation of stationary digital chest tomosynthesis in adult patients with cystic fibrosis

Abstract: We are requesting dual first authorship for E. Taylor Gunnell and Dora Franceschi. These students contributed equally to the design, implementation, analysis, and write up of this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…New advancements in carbon nanotube technology have allowed a linear X‐ray imaging array to be substituted for the conventional moving X‐ray source to provide X‐ray projections from multiple directions. Thus, sequential activations of a carbon nanotube linear X‐ray source allows for image acquisition without the need for motion, thus reducing the chance of blur artifact 16,17 . This provides high‐resolution coronal images of the chest with approximately 1/10th of the radiation dose of a typical CT scan (Figure 1).…”
Section: Chest Tomosynthesismentioning
confidence: 99%
See 2 more Smart Citations
“…New advancements in carbon nanotube technology have allowed a linear X‐ray imaging array to be substituted for the conventional moving X‐ray source to provide X‐ray projections from multiple directions. Thus, sequential activations of a carbon nanotube linear X‐ray source allows for image acquisition without the need for motion, thus reducing the chance of blur artifact 16,17 . This provides high‐resolution coronal images of the chest with approximately 1/10th of the radiation dose of a typical CT scan (Figure 1).…”
Section: Chest Tomosynthesismentioning
confidence: 99%
“…The chest tomosynthesis image (C) was scored as 14 on tomosynthesis scoring system and demonstrated bronchial wall thickening (white circle), bronchiectasis (black circle), and mucus plugging (white arrow). Reprinted, in part, with permission by Springer Nature (Gunnell et al 16 ). CF, cystic fibrosis; CT, computed tomography; CXR, chest radiography; FEV 1 , forced expiratory volume in 1 second…”
Section: Chest Tomosynthesismentioning
confidence: 99%
See 1 more Smart Citation
“…This has led to the development of a variety of electron sources for x‐ray generation, such as carbon nanotube (CNT)‐based field emitters, 13 tungsten dispenser cathodes, 14 and Spindt type emitters 15 . Recently, spatially distributed x‐ray source array technology with CNT field emitters has been demonstrated for a variety of 3D imaging applications 16–19 . Featuring source‐to‐source distances as low as 4 mm, these unique switching x‐ray systems are well suited to provide the necessary angular resolution for CT imaging.…”
Section: Introductionmentioning
confidence: 99%
“…( 26 ) A recent study reported good correlation between the tomosynthesis scoring and Brasfield score. ( 27 ) However, there are no available studies comparing DTS and CT regarding quantitative surveillance of structural lung disease in CF.…”
Section: Introductionmentioning
confidence: 99%